Shrinking agriculture in the arid landscapes of the Cholistan Desert: a geospatial assessment of urban expansion and its implications for the sustainable future of Multan City, Pakistan - Hussain , Muhammad; Shaikh , Saima; Ahmad, Zahir; Ihsanullah,; Kontakiotis, George; Dittmann, Andreas (Ecological Questions, 2026)
Pakistan is an agro-based country, and the majority of its population depends on agriculture for survival. Currently, sporadic urban expansion is a serious threat to urban agriculture, the environment, food security, and livelihood sustainability. This study aims to explore the dynamics of urban expansion patterns and their intricate interplay with agricultural land, focusing on their ramifications and future urban land-use predictions. For this purpose, remotely sensed data spanning 30 years from 1990 to 2020 and secondary data from the DCR and the Pakistan Bureau of Statistics are used. The collected data were analyzed through advanced geospatial techniques, CAM, and statistical techniques. The built-up area was observed 75 km2 in 1990 to 299 km2 in 2020. Furthermore, the annual increase is 9.5%. This haphazard growth converts approximately 31% (100 km2) of Multan city's fertile agricultural lands into a built-up environment, and the CA Markov model predicts that the built-up area will further increase by 54% in 2030 and 67% in 2040. The correlation between built-up and agricultural areas is strongly positive. The study provides nuanced insights for policymakers, land managers, and urban planners to formulate better policies for regulating sustainable urban expansion and fostering resilient urban development.